Enzyme catalyzed oxidative humification reactions (ECOHRs): PFAS remediation and thatch management - Munir, Umar; Wang, Yifei; Huang, Qingguo (Frontiers in Environmental Engineering, 2025)
Enzyme-Catalyzed Oxidative Humification Reactions (ECOHRs) are primarily recognized for their involvement in the degradation of lignin. Lignolytic fungi produce extracellular enzymes under nutrient-deficient conditions, which can act directly or indirectly through small-molecule mediators to modify a range of compounds in the environment. The enzymes mediating ECOHRs mainly include laccases, lignin peroxidases (LiP), and manganese peroxidases (MnP), whose properties and catalysis mechanisms are summarized and compared in this review. As an example showcasing the possible environmental application of ECOHRs, the effects of ECOHRs in mediating the transformation of two key per- and polyfluoroalkyl substances (PFAS), perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS), were discussed. Reports have shown their significant concentration reduction (40%–59%) in systems with ECOHRs induced by amendments with laccases and mediators. Nontarget products identification using high-resolution mass spectrometry suggests that PFOA and PFOS degraded in ECOHR systems primarily through free-radical chain reactions. Reports on the use of laccase to reduce and manage the thatch layer on turf grass are also discussed in this review as another example of ECOHRs application. Laccase application at a rate of 2 U/cm2 once per month was found to be as effective as traditional thatch management methods, with the ECOHR effects leading to a reduction in the thatch thickness by 18%–22% in bermudagrass and 21%–30% in zoysiagrass. Overall, this review addresses the concept of ECOHRs, with the major enzymes and systems introduced, and highlights their possible environmental applications exemplified by PFAS remediation and thatch management.